Alternative Treatment Approaches For The Management Of Diabetes: Role Of Soursop Leaves And Spirulina As Antidiabetic Agents (International Journal of Food and Nutritional Sciences, 2022)
Diabetes mellitus (DM) is a metabolic disorder characterized by blood glucose levels that are consistently high. Different medicinal approaches may be used to address this complex medical condition. Herbal formulations and extracts are gaining popularity as a means of treating type 2 diabetes (T2DM). Therefore, the purpose of this research is to examine the efficacy of spirulina and powdered soursop leaves as dietary supplements for the treatment of diabetes. Thirty individuals with type 2 diabetes mellitus were randomly assigned to one of three groups: Experimental Group I (SP), which received Spirulina powder (SP), Experimental Group II (SLP), which received Soursop leaves powder (SLP), and Control Group (placebo). There were several preexisting similarities between the control and research groups. Multiple criteria were used to evaluate the efficacy of administering 2 grams of supplementations twice a day for three months. A nutritional study of the supplements showed that the powdered spirulina is high in calories, carbohydrates, proteins, lipids, iron, and magnesium, whereas the powdered soursop leaves had a high moisture content, ash content, and crude fiber content. The microbiological analysis discovered no significant differences between the two supplements. The phytochemical analysis revealed a high phenolic and flavonoid content in the soursop leaf powder. The anthropometric study yielded similar results for SP and SLP. Diabetic subjects' lipid profiles (TCH, HDL, LDL, VLDL, and TGL) and blood glucose levels (FBG, PPBGC, and glycosylated hemoglobin, HbA(1c)) were measured before and after the supplementation. After 3 months of supplementation with powdered soursop leaves, both fasting and postprandial blood glucose levels were considerably reduced. The HbA(1c) level also decreased significantly, which is indicative of better long-term glucose management. Triglyceride levels dropped significantly compared to lipid levels. The participants who were given spirulina powder had substantial increases in high-density lipoprotein (HDL) and decreased levels of total cholesterol (TC), low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL). Evaluation of clinical symptoms and problems post-intervention revealed that spirulina supplementation successfully reduced symptoms and complications. These findings provide evidence in favor of the effectiveness of spirulina powder in improving the lipid profile and soursop leaf supplementation in decreasing blood glucose levels in individuals with type 2 diabetes mellitus.